PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI DINAS PENDIDIKAN PROVINSI RIAU - Sukarja, Rahmat (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the influence of leadership and communication on jobsatisfaction and employee performance Riau Provincial Education Department. The method of analysisused in this study is a descriptive statistical analysis and path analysis (path analysis).Collecting data using questionnaires and surveys with sampling done by stratified random samplingfrom a population where 188 employees, the sample used is as much as 128 respondents.Prior to test the hypothesis, the data of respondents through some statistical data processing, amongothers: the transformation of ordinal data into interval data, validity and reliability of data, suchassumption; test for normality, linearity test, test homoskedastisitas, and multicollinearity test. Thenproceed with the analysis of the path (path analysis).And based on the results of statistical analysis has been done, the results are as follows, namely: thatthe leadership and communication factors simultaneously and partial direct and significant impact onjob satisfaction. It further found that the factor of leadership, communication and job satisfactionsimultaneously direct significant effect on employee performance. This is not in line for the partialeffect, where the results obtained show that the only factor that job satisfaction is directly significanteffect on employee performance. As for leadership and communication factor was found only to have asignificant effect on performance is indirect through job satisfaction variables.Keywords: Leadership, Communication, Job Satisfaction, and Performance.